Adaptasi Mahasiswa Keperawatan Angkatan 2020 Di Salah Satu Universitas Swasta Indonesia Bagian Barat - Peggy Tahulending; Defitaria Panggabean; Riris Jatining Panglipur; Suge Tertia Orlen Zeva; Kusman Sudarja (Jurnal Keperawatan Malang, 2023)
Background: Adaptation is important for adjustment to change. A student who is pursuing education needs the ability to cope with the changes that occur. Students' inability to adapt has an impact on academic, social adjustment, personal-emotional adjustment, and institutional attachment. Objectives: To describe the adaptation nursing student class of 2020 at one of the Western Indonesian Private Universities. Methods: This study uses a quantitative descriptive method with a cross sectional approach. Population in this study 231 students. Instruments used adapted from the Student Adjustment to College Questionnaire (SACQ). The data analysis technique used is univariate analysis with conducting data from January to April 2022. Results: adaptation of nursing students class of 2020 in college at one of the western Indonesian private universities shows that 147 students obtained moderate results on the four subscales, first academic adjustment (66.7%), social adjustment (81%), personal-emotional adjustment (68%), and institutional attachment (57.8%). Students' Academic Adjustment abilities showed the highest percentage (19.7%) among others subscale and Institutional Attachment abilities showed the lowest percentage (29.3%). Recommendation: In the form of a special basic training program to discuss how to adapt properly in the university environment.